“No chronicle records his fellow”: Reading Perkin Warbeck in the Early Seventeenth Century - Djordjevic, Igor (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2017)
This article argues that John Ford’s play Perkin Warbeck should be read in the context of “new” Jacobean readings of the historiography of Henry VII’s reign. After tracing the origins and dissemination of Warbeck’s scaffold confession of imposture, and exposing the sixteenth-century chroniclers’ reliance on mind-reading, clairvoyance, fallacious reasoning, and shrill invective, the article reveals the revaluation of this received “memory” of the 1490s by influential seventeenth-century historians. I argue that Ford’s elimination of the confession and his strategy of staging realpolitik as a kind of non sequitur response to the audience’s persistent questions regarding the “truth” of Perkin’s identity return the story to the indeterminacy it had for its contemporaries.